Immunotherapy: is a minor god yet in the pantheon of treatments for lung cancer?. Issue 10 (October 2014) - Rolfo, Christian; Sortino, Giovanni; Smits, Evelien; Passiglia, Francesco; Bronte, Giuseppe; Castiglia, Marta; Russo, Antonio; Santos, Edgardo S; Janssens, Annelies; Pauwels, Patrick; Raez, Luis
<x xml:space="preserve">Abstract</x> Immunotherapy has been studied for many years in lung cancer without significant results, making the majority of oncologists quite skeptical about its possible application for non-small cell lung cancer treatment. However, the recent knowledge about immune escape and subsequent 'cancer immunoediting' has yielded the development of new strategies of cancer immunotherapy, heralding a new era of lung cancer treatment. Cancer vaccines, including both whole-cell and peptide vaccines have been tested both in early and advanced stages of non-small cell lung cancer. New immunomodulatory agents, including anti-CTLA4, anti-PD1/PDL1 monoclonal antibodies, have been investigated as monotherapy in metastatic lung cancer. To date, these treatments have shown impressive results of efficacy and tolerability in early clinical trials, leading to testing in several large, randomized Phase III trials. As these results will be confirmed, these drugs will be available in the near future, offering new exciting therapeutic options for lung cancer treatment.